Biocompatibility evaluation of zeolite compared to bone HA, calcium phosphate (Ca2PO4) and eugenol paste - (:unkn) unknown (Trans Tech Publications Ltd, 2005)
The biocompatibility of Zeolite was evaluated, in vitro, compared to a control and to three different biomaterials: hydroxyapatite from bovine bone, calcium phosphate and a commercial eugenol paste. The Zeolite did not affect cellular proliferation neither the alkaline phosphatase and collagen production. The apoptosis index of the zeolite groups were similar to control and optical microscopy observations did not show any morphological cell change, except the some cytoplasmatic vacuole formation.
Keywords: Apoptosis; Clinoptilolite; Eugenol paste; Osteoblast; Zeolite